2015
DOI: 10.1088/2040-8978/17/2/025702
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg grating based notch filter for bit-rate-transparent NRZ to PRZ format conversion with two-degree-of-freedom optimization

Abstract: We propose a novel notch-filtering scheme for bit-rate transparent all-optical NRZ-to-PRZ format conversion. The scheme is based on a two-degree-of-freedom optimally designed fiber Bragg grating. It is shown that a notch filter optimized for any specific operating bit rate can be used to realize high-Q-factor format conversion over a wide bit rate range without requiring any tuning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The authors [4] have proposed and demonstrated experimentally a novel optimally designed FBG-filter scheme, which is based upon single fibres and designed for the conversion from RZ-OOK/DPSK/DQPSK to NRZ-OOK/DPSK/DQPSK format. A novel notchfiltering scheme, which is based on an optimally designed two-degree-of-freedom FBG, has been suggested for a transparent all-optical bit-rate NRZ-to-PRZ format conversion [5]. The existence, stability and collision dynamics of moving Bragg-grating solitons in a semi-linear dual-core system have been analyzed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [4] have proposed and demonstrated experimentally a novel optimally designed FBG-filter scheme, which is based upon single fibres and designed for the conversion from RZ-OOK/DPSK/DQPSK to NRZ-OOK/DPSK/DQPSK format. A novel notchfiltering scheme, which is based on an optimally designed two-degree-of-freedom FBG, has been suggested for a transparent all-optical bit-rate NRZ-to-PRZ format conversion [5]. The existence, stability and collision dynamics of moving Bragg-grating solitons in a semi-linear dual-core system have been analyzed in Ref.…”
Section: Introductionmentioning
confidence: 99%